International and multi-institutional assessment of factors associated with performance and quality of lymph node dissection during radical nephrectomy - Osterberg, E. Charles; Golan, Shay; del Pilar Laguna Pes, Maria; Eggener, Scott E.; Petrut, Bogdan; Singh, Shrawan Kumar; Sountoulides, Petros; Türkeri, Levent; Wolf, J. Stuart Jr. (Elsevier Science Inc., 2019)
Objective: To determine factors associated with performance and quality of lymph node dissection during radical nephrectomy. Materials and Methods: Using an International Data Registry, we performed multilevel logistic regression to determine the association of surgical approach (open surgery vs minimally invasive surgery), institutional experience (low, moderate, and high tertiles), and institutional preference (minimally invasive surgery, balanced, and open surgery tertiles) with the performance of lymph node dissection in subgroups by clinical stage and nodal status. Results: Among 1,742 patients undergoing radical nephrectomy, 312 (18%) underwent lymph node dissection, which was associated with stage (28% for ?cT2 vs 9.3% for cT1), and nodal status (68% for ?cN1 vs 13% for cN0). Open surgery was significantly associated with performing lymph node dissection in all subgroups. Institutional experience and institutional preference had no association with performing lymph node dissection in the ?cN1 group. The number of nodes removed was greater for open surgery (mean 5.9) vs minimally invasive surgery (mean 3.4); this held true even when stratified by stage and nodal status. Conclusion: In this large dataset, open surgical radical nephrectomy is associated with more frequent performance and higher quality of lymph node dissection, which may owe to selection bias but also could reflect technical concerns. In the patient population in whom lymph node dissection is recommended (?cN1), this is not explained by institutional experience or preference. Lymph node dissection may be under-utilized for ?cN1 disease and over-utilized for cN0 disease, at least according to practice guidelines.
Keywords: Radical Nephrectomy; Lymph Node; Assessment